Challenges of transitioning from a faculty to an administrative role: part 3, from solving problems to managing polarities. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
3 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Health & Human Services, Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Education; Nursing; *Efficiency; Organizational; *Faculty; Nursing; *Leadership; *Nurse Administrators; *Professional Role/px [Psychology]; Curriculum; Education; Nursing; Efficiency; Organizational; Faculty; Nursing; Humans; Leadership; Nurse Administrators; Professional Role; Time Factors; article; curriculum; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; professional standard; psychological aspect; time

Challenges of transitioning from a faculty to an administrative role: part 2, moving from individual contributor to group leader. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
1 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Health & Human Services, Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Faculty; Nursing; *Group Processes; *Leadership; *Nurse Administrators; Education; Nursing; Faculty; Nursing; Group Processes; Humans; Leadership; Nurse Administrators; Schools; Nursing; Social Support; article; dept.aa; group process; human; leadership; nurse administrator; nursing education; peer-reviewed; social support

Transitioning from a faculty to an administrative role: part 1, moving from individual to collective accountability. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
2 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Graduate Studies, Southern Connecticut State University, New Haven, USA.
Keywords: *Career Mobility; *Faculty; Nursing/og [Organization & Administration]; *Nurse Administrators/og [Organization & Administration]; *Professional Role; Career Mobility; Employee Performance Appraisal; Faculty; Nursing; Humans; Leadership; Nurse Administrators; Professional Role; United States; article; career mobility; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; personnel management; professional standard